Outcomes of decreasing versus increasing cardiac troponin in patients admitted with non-ST-segment elevation myocardial infarction: the Atherosclerosis Risk in Communities Surveillance Study. Issue 9 (8th April 2019) - Arora, Sameer; Cavender, Matthew A; Chang, Patricia P; Qamar, Arman; Rosamond, Wayne D; Hall, Michael E; Rossi, Joseph S; Kaul, Prashant; Caughey, Melissa C
Abstract: Background: The fourth universal definition of myocardial infarction requires an increase or decrease in cardiac troponin for the classification of non-ST-segment elevation myocardial infarction. We sought to determine whether the characteristics, management, and outcomes of patients admitted with non-ST-segment elevation myocardial infarction differ by the initial biomarker pattern. Methods: We identified patients in the Atherosclerosis Risk in Communities Surveillance Study admitted with chest pain and an initially elevated cardiac troponin I, who presented within 12 hours of symptom onset and were classified with non-ST-segment elevation myocardial infarction. A change in cardiac troponin I required an absolute difference of at least 0.02 ng/mL on the first day of hospitalization, prior to invasive cardiac procedures. Results: A total of 1926 hospitalizations met the inclusion criteria, with increasing cardiac troponin I more commonly observed (78%). Patients with decreasing cardiac troponin I were more often black (45% vs. 35%) and women (54% vs. 40%), and were less likely to receive non-aspirin antiplatelets (44% vs. 63%), lipid-lowering agents (62% vs. 80%), and invasive angiography (38% vs. 64%). Inhospital mortality was 3%, irrespective of the cardiac troponin I pattern. However, patients with decreasing cardiac troponin I had twice the 28-day mortality (12% vs. 5%; P =0.01). Fatalities within 28 days were more often attributable to non-cardiovascular causes in those with decreasing versus increasing cardiac troponin I (75% vs. 38%; P =0.01). Conclusion: Patients presenting with chest pain and an initially elevated cardiac troponin I which subsequently decreases are less often managed by evidence-based therapies and have greater mortality, primarily driven by non-cardiovascular causes. Whether associations are attributable to type 2 myocardial infarction or a subacute presentation merits further investigation.